2019
DOI: 10.1021/acs.langmuir.9b01691
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Surface Charge Can Immobilize the Air/Water Interface

Abstract: Recent Surface Force Apparatus measurements on thin film drainage as a bubble approaches a surface are reinterpreted in terms of a new model for the air/water interface. In this model, surface charge at the interface can be convected and can diffuse along the surface as the film drains. This creates surface tension gradients, since surface tension includes a charge-dependent contribution from the double-layer free energy. Although this electrocapillary effect is relatively small, we show here that the gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Yang et al recently demonstrated better agreement with modeling and experiments using a no-slip boundary condition for capillary-driven flow in microchannels . This liquid–gas interface immobilization finding is not unique , but also not uncontested . Marangoni effects, due to surface tension gradients, have been suggested as one possible explanation for how the liquid–air interface could be immobilized .…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Yang et al recently demonstrated better agreement with modeling and experiments using a no-slip boundary condition for capillary-driven flow in microchannels . This liquid–gas interface immobilization finding is not unique , but also not uncontested . Marangoni effects, due to surface tension gradients, have been suggested as one possible explanation for how the liquid–air interface could be immobilized .…”
Section: Introductionmentioning
confidence: 78%
“…21 This argument is made in the context of prior literature, which has demonstrated how surface tension gradients can lead to no-slip behavior and the mechanisms that can generate surface tension gradients including surfactant contamination 23 or mobile surface charge. 22 Because of heating in our tests, there also must be surface tension gradients present because of the temperature dependence of water surface tension. This thermal-driven effect in porous media is well-known and can give rise to Marangoni convective flows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The motion of gas bubbles is known to be affected by even the smallest amount of surface-active impurities, as these molecules adsorb at the gas-liquid interface and change the tangential mobility at the bubble surface [1][2][3]. In high-purity water (or surface-active molecule free) electrolyte solutions, in the low shear stress case (i.e., smaller bubbles or gasliquid interface moving slowly), the gas-liquid interface deviates from being tangentially mobile [4][5][6][7][8]. For the higher shear stress (i.e., larger bubbles or gas-liquid interface moving fast) the gas-liquid interface stays tangentially mobile [9,10].…”
Section: Introductionmentioning
confidence: 99%